STRATEGI KREATIF DOSEN MEMACU PARTISIPASI MAHASISWA DALAM MENGIKUTI PERKULIAHAN - Nengah Sukendri; Ni Luh Eka Yuli Anggreni (Institut Agama Hindu Negeri Gde Pudja Mataram, 2022)
Learning is one of the manifestations of respect for the teacher of recitation where this is realized by an effort to learn science. The purpose of this study is to find out and describe what obstacles students face in attending lectures and how the lecturer's creative strategies stimulate student participation in attending lectures. The study used a qualitative research methodology studied with Educational theory and Behavioristic theory. The results of the research include: student obstacles in attending lectures, namely: 1) physiological factors from within students, namely because they are sick, unhealthy and have physical disabilities. Psychologically, the most important thing is study habits, lack of confidence and difficulty in managing time. 2) external factors, namely the lack of facilities in learning, motivation, economy, lack of socialization so that it is difficult to make friends or adapt both to lecturers and to learning that is followed during lectures. The lecturer's creative strategy stimulates student participation in attending lectures, including: 1). punctuality, firmness and mutual agreement between lecturers and students both for arrival hours, lectures and also agreements in collecting assignments. 2). submission of lecture contracts, so that there are no protests from students, no students repeating courses, 3). learning methods, and periodically changing learning media, 4). hold quizzes, exercises or impromptu games. 5). reminding students the importance of participating in lectures and doing coursework. ask for explanations and what obstacles students experience during the lecture, not demeaning students' abilities or looking down on student behavior.